Pengaruh Celebrity Endorser, Brand Image, dan Kualitas Produk terhadap Keputusan Pembelian Produk Skincare Somethinc di Purwokerto - Evanthi, Olivia Dea; Hidayah, Arini; Rachmawati, Erny; Endratno, Hermin (Universitas Batanghari, 2024)
This study attempts to look at how consumer decisions about Somethinc Skincare Products in Purwokerto are influenced by celebrity endorsements, brand perceptions, and product quality. To distribute surveys and gather quantitative data, the researchers utilized google forms. The group under research is made up of Purwokerto individuals who have purchased Somethinc skincare products. This sampling strategy combines a purposive sampling approach with non-probability sampling methods. The sample size was determined by utilizing the Roscoe approach to poll 110 people in total. This study makes use of descriptive statistics, hypothesis testing, testing of instruments, testing of classical assumptions, testing of goodness of fit, and testing of instruments. This study use multiple linear regression analysis as its method of data analysis. This study used the SPSS 26 statistical package to handle the data. According to this study's findings, Somethinc skincare products in Purwokerto are more likely to be purchased when the following factors are considered: celebrity endorsement, brand image, and product quality.